Promotion and Product Quality in Determining Purchase Decision Smartphone Xiaomi - Apryani Nurunnisha, Gina; Wira Pratama, Rio (International Journal of Psychosocial Rehabilitation, 2020)
This study revealed a gap between the lack of promotion and poor quality of Xiaomi smartphone products, but Xiaomi smartphone sales increased significantly from 3 percent to 25 percent in the Indonesian market. This study aims to determine whether promotion and product quality affect purchasing decisions of Xiaomi smartphones. The factors tested in this study were promotion and product quality as an independent variable, while purchasing decisions as the dependent variable. The research method used is the descriptive method, with data collection techniques through observation and questionnaire distribution. The population of this research is Widyatama students who use Xiaomi smartphones; the research sample is 150 respondents. Data analysis uses multiple linear regression analysis at a significant level of 5 percent. The program used SPSS 25 and Lisrel 8.80. The results showed two independent variables, namely promotion and product quality, did not significantly influence the purchasing decisions of Widyatama students who used Xiaomi smartphones.